The Relationship between OSIS Organizational Activity and Student Learning Outcomes at SMPN 34 Padang City - Haqqi, Raju; Wisroni, Wisroni (Universitas Negeri Padang, 2023)
This research is backround by the lack of interest and motivation in learning of students, and students are more preoccupied with student council activities. The purpose of this research is to find out the description and whether there is a relationship between the activeness of student council organizations and student learning outcomes. The type of research used is correlational with a quantitative approach. With a population of all OSIS administrators at SMPN 34 Kota Padang, totaling 36 people consisting of 21 class VII students and 15 class VIII students. While taking samples using stratified random sampling technique. In this study there were two strata, namely class VII and VIII. So, the sample taken is 70% of the class level. Where the sample is 15 class VII and 11 class VIII with a total sample of 26. The data collection technique is a questionnaire or questionnaire. The collected data were analyzed using the proportion formula and rank order. The results of the study show that the results of the research data management and discussion that have been described in the previous chapter, it can be concluded (1) Members and OSIS administrators of SMPN 34 Padang City are included in the active category. Where the level of attendance in OSIS activities is high, is responsible for the position held, dares to provide suggestions, criticism and opinions in good and polite language, has a willingness to sacrifice, and has high motivation to increase self-confidence and potential that exists within. (2) The learning outcomes of students who become members and administrators of the OSIS are modified into the good category with the lowest score of 72.10 and the highest score of 84.70 (3) There is a moderate positive relationship between the activeness of OSIS organizations and student learning outcomes. this is seen from the significant value of 0.002. Where 0.002 <0.05 and the tcount value is 0.586 which is in the medium category.